Keabsahan Perkawinan terhadap Suami Murtad (Riddah) ke dalam Khonghucu dengan Identitas Muslim - Diastata Orshita Putri Dewanty; Adina Hasani (Jurnal Hukum Lex Generalis, 2026)
Confucianism is a legally recognized religion in Indonesia pursuant to Presidential Decree Number 6 of 2000 concerning the Revocation of Presidential Instruction Number 14 of 1967 on Religion, Beliefs, and Chinese Customs. This condition gives rise to legal issues when an individual who is administratively registered as a Muslim, but in fact commits riddah by reverting to Confucian teachings. The legal issues concern the validity of marriage and the authority of a marriage guardian (wali nikah) over a daughter from the perspective of Islamic law and Indonesian positive law. The findings indicate that, under Islamic law, riddah results in the dissolution of marriage and the loss of the father’s authority as a marriage guardian due to the failure to meet the requirement of being Muslim. However, under Indonesian positive law, the marriage remains legally valid insofar as there has been no final and binding court decision. This discrepancy reflects a lack of harmonization between Islamic legal norms and national law, which may lead to legal uncertainty in practice.